PENILAIAN MEMORABLE TOURISM EXPERIENCE SEBAGAI FAKTOR PENENTU DAYA SAING DESTINASI WISATA DENGAN MENGGUNAKAN PENDEKATAN RAPID APPRAISAL (RAP) - Ardiansyah Muhammad; Siti Aisjah; Ainur Rofiq (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. The purpose of this study is to describe the assessment of competitiveness of tourist destinations through memorable tourism experience as a factor determining the competitiveness of tourist destinations. This study also aims to assess the competitiveness of Banyuwangi based on through memorable tourism experience provided to tourists. Sample in this study were 96 tourists. Sampling technique used was snowball sampling. Rapid Appraisal (RAP) approach is used as a tool to analyze the competitiveness of tourist destinations. The Rapid Appraisal (RAP) in thid research called Rapid Appraisal for Tourism Destination Competitiveness (RAP-TDC). RAPTDC consists of 3 statistical analyzes: Multidimensional Scalling, Montecarlo, and Jacknife. The results showed that Banyuwangi has a good competitiveness based on memorable tourism experience given to tourists. Novelty is an attribute of memorable tourism experience that has the greatest role in influencing the assessment of tourists to tourist destinations. The uniqueness of the travel experience is the most important indicator in shaping the novelty of the experience in the tour.